Site Index Equations for Eucalyptus Hybrid in Punjab - Dogra, A. S.; Upadhyay, Anoop (Indian Forester, 2005)
Punjab is a major Eucalyptus growing State but no height-age equations have been developed for the species using permanent sample plot data from the region and after testing a wide variety of linear and non-linear growth functions. As site index equations differ by tree species and region, the objective of the present study is to develop site index equations for Eucalyptus hybrid in Punjab using permanent sample plot data. Data from 133 permanent experimental plots with age and top heights ranging from 3.9 to 11 years and 6 to 26.2 meters respectively were used for estimating the parameters of three linear and six non-linear growth functions. A generalized variant of Schumacher's non-linear equation was found to give the best fit. It was also found that the top heights of Eucalyptus in Punjab were better above the chosen reference age of six years, than those of Uttar Pradesh as depicted in the top height-age tables given by Chaturvedi for different site qualities.